The novel flavone tetramethoxyluteolin is a potent inhibitor of human mast cells - Weng, Zuyi; Patel, Arti B.; Panagiotidou, Smaro; Theoharides, Theoharis C. (Journal of allergy and clinical immunology, 2015)
Mast cells (MCs) are hematopoietic cells that mature in tissues and are involved in allergy, immunity, and inflammation by secreting multiple mediators. The natural flavone luteolin has anti-inflammatory actions and inhibits human mast cells (MCs). We sought to investigate the ability of luteolin and its novel structural analog 3′,4′,5,7-tetramethoxyluteolin (methlut) to inhibit human MC mediator expression and release in vitro and in vivo. Human LAD2 cells and umbilical primary human cord blood–derived cultured mast cells were stimulated with substance P (SP) or IgE/anti-IgE with or without preincubation with luteolin, methlut, or cromolyn (1-100 μmol/L) for 2 or 24 hours, after which mediator secretion was measured. The effect of the compounds on MC intracellular calcium levels and nuclear factor κB activation was also investigated. Pretreatment with methlut was also studied in mice passively sensitized with dinitrophenol–human serum albumin and challenged intradermally. Methlut is a more potent inhibitor than luteolin or cromolyn for β-hexosaminidase and histamine secretion from LAD2 cells stimulated by either SP or IgE/anti-IgE, but only methlut and luteolin significantly inhibit preformed TNF secretion. Methlut is also a more potent inhibitor than luteolin of de novo–synthesized TNF from LAD2 cells and of CCL2 from human cord blood–derived cultured MCs. This mechanism of action for methlut might be due to its ability to inhibit intracellular calcium level increases, as well as nuclear factor κB induction, at both the transcriptional and translational levels in LAD2 cells stimulated by SP without affecting cell viability. Intraperitoneal treatment with methlut significantly decreases skin vascular permeability of Evans blue dye in mice passively sensitized to dinitrophenol–human serum albumin and challenged intradermally. Methlut is a promising MC inhibitor for the treatment of allergic and inflammatory conditions.